Design optimality criteria and restrictions for the protection of information systems - Хохлачова, Юлія Євгеніївна (Ukrainian Information Security Research Journal, 2012)
This article deals with the important and topical issue of construction procedures formalizing performance criteria and constraints. A development and application of axiomatic theory for the mathematical modeling of optimality criteria and constraints as certain features of managed well and uncontrolled variables. Governed and reviewed in detail the system of rules (axioms) mathematical modeling of optimality criteria and constraints, which is based on the necessary conditions for the existence of reliable and extrema of functions and functionals. Shows a number of distinct advantages that are mathematical models of criteria and constraints.